First report of cassava mosaic disease and cassava mosaic geminiviruses in Gabon - Legg, James P.; Ndjelassili, F.; Okao-Okuja, G. (Wiley, 2004)
Cassava mosaic disease (CMD), arguably Africa's greatest plant protection problem, has been known to occur in central/West Africa for more than 70 years. There is, however, no published record of the occurrence of CMD or the cassava mosaic geminiviruses (CMGs) that cause it from the central African country of Gabon. Significantly, however, the severe Uganda variant of East African cassava mosaic virus (EACMV-UG), associated with the African CMD pandemic, has been recorded from the Republic of Congo (Neuenschwander et al., 2002), bordering Gabon to the west.